The Effectiveness of Warm and Cold Compress In The Implementation Of Pain After DPT - Hb – Hib Immunization At BPM “D” Of Neglasari Sub-District Tangerang City In 2021 - Risza Choirunissa; Retno Widowati; Hery Putri Anandah (Universitas STRADA Indonesia, 2021)
The research design used a Quasi-Experimental with two group pretest posttest designs. The instrument used was the FLACC scale to assess the condition of the infants before and after compressing and immunization, in which cold compress carried out 10 minutes before the immunization, while warm compress were carried out 15 minutes before immunization. The data distribution was tested using the Shapiro-Wilk test, Wilcoxon test and Mann Whitney test. The Wilcoxon test results showed that both of them have an effect on pain by getting the sig value. of 0.001 ≤ 0.05. Based on Whitney's mann test analysis, the mean difference of before and after the warm compress was 23, while before and after the cold compress was 8. The comparison of the effectiveness of warm compress and cold compress in pain management had a p-value of 0.000 indicating that there was an influence in pain management.